Associating local strains to global pressure–volume mouse lung mechanics using digital image correlation. Issue 19 (7th October 2022) - Nelson, Talyah M.; Quiros, Kathrine A. M.; Mariano, Crystal A.; Sattari, Samaneh; Ulu, Arzu; Dominguez, Edward C.; Nordgren, Tara M.; Eskandari, Mona
Abstract: Pulmonary diseases alter lung mechanical properties, can cause loss of function, and necessitate use of mechanical ventilation, which can be detrimental. Investigations of lung tissue (local) scale mechanical properties are sparse compared to that of the whole organ (global) level, despite connections between regional strain injury and ventilation. We examine ex vivo mouse lung mechanics by investigating strain values, local compliance, tissue surface heterogeneity, and strain evolutionary behavior for various inflation rates and volumes. A custom electromechanical, pressure–volume ventilator is coupled with digital image correlation to measure regional lung strains and associate local to global mechanics by analyzing novel pressure–strain evolutionary measures. Mean strains at 5 breaths per minute (BPM) for applied volumes of 0.3, 0.5, and 0.7 ml are 5.0, 7.8, and 11.3%, respectively, and 4.7, 8.8, and 12.2% for 20 BPM. Similarly, maximum strains among all rate and volume combinations range 10.7%–22.4%. Strain values (mean, range, mode, and maximum) at peak inflation often exhibit significant volume dependencies. Additionally, select evolutionary behavior (e.g., local lung compliance quantification) and tissue heterogeneity show significant volume dependence. Rate dependencies are generally found to be insignificant; however, strain values and surface lobe heterogeneity tend to increase with increasing rates. By quantifying strain evolutionary behavior in relation to pressure–volume measures, we associate time‐continuous local to global mouse lung mechanics for the first time and further examine the role of volume and rate dependency. The interplay of multiscale deformations evaluated in this work can offer insights for clinical applications, such as ventilator‐induced lung injury. Abstract : Topological strain contours for representative mouse at various inflation volumes and frequencies